COMPARATIVE STUDY OF ANTIBACTERIAL ACTIVITY OF PHOTOACTIVATED DISINFECTION WITH FOTOSAN AND STANDARD ENDODONTIC TREATMENT - Tzvetelina G. Gueorgieva; Raina T. Gergova (Peytchinski Publishing, 2021)
Introduction: The purpose of endodontic treatment is to eliminate the bacterial infection in the root canal system and allow healing of apical periodontitis. Sometimes the anatomical complexity of the root canal system makes complete removal of bacteria almost impossible even if the conventional methods of chemo-mechanical debridement are performed strictly according to the protocol. So additional methods of root canal disinfection can be applied such as photoactivated disinfection (PAD). Purpose: The aim of our study was to compare the antibacterial activity of PAD with FotoSan, and conventional endodontic therapy in the treatment of infected root canals. Materials and methods: The study involved 36 teeth of patients who are diagnosed with pulp necrosis or with the periapical chronic periodontitis and require endodontic treatment and divided into two groups of 18 teeth each. The first microbiological sample was taken by placing a sterile paper point in the root canal, after endodontic access cavity preparation. All root canals are prepared by Protaper Universal rotary instruments (Maillefer Instruments SA, Ballaigues, Switzerland). In the first group, the disinfection of the root canals was made with photoactivated disinfection with FotoSan. In the second group was performed the endodontic treatment with the standard protocol of irrigation - 2.5% sodium hypochlorite solution and 17% EDTA. After that, the root canals are dried with sterile points, and a second microbiological sample is taken. Results: In all compared pairs, there was no significantly different effect regarding the number of microorganisms. Conclusions; The disinfection with NaOCl has the strongest antimicrobial effect in this study. Second place is occupied by PAD with FotoSan. We believe that the established antimicrobial effect of PAD make the method appropriate as complementary to routine endodontic treatment.